2016
DOI: 10.1038/srep24241
|View full text |Cite
|
Sign up to set email alerts
|

In vivo imaging demonstrates dendritic spine stabilization by SynCAM 1

Abstract: Formation and stability of synapses are required for proper brain function. While it is well established that synaptic adhesion molecules are important regulators of synapse formation, their specific role during different phases of synapse development remains unclear. To investigate the function of the synaptic cell adhesion molecule SynCAM 1 in the formation, stability, and maintenance of spines we used 2-photon in vivo imaging to follow individual spines over a long period of time. In SynCAM 1 knockout mice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 35 publications
(52 reference statements)
0
9
0
Order By: Relevance
“…The mechanism linking LTP to synaptic stabilization, and LTD to destabilization, is likely to involve several processes. Synaptic tenacity is known to be affected by trans-synaptic proteins such as Neuroligin-1 and SynCAM-1 ( Zeidan and Ziv, 2012 ; Körber and Stein, 2016 ), PSD-95 ( De Roo et al, 2008 ; Cane et al, 2014 ), ubiquitin protein ligase E3A ( Kim et al, 2016 ), ensheathment of the synapse by astrocyte processes ( Bernardinelli et al, 2014 ) and many other local factors. It may be a combination of local physical changes and distributed network effects, such as the recurrent reactivation of a specific circuit ( Wei and Koulakov, 2014 ; Novitskaya et al, 2016 ), which makes once potentiated synapses robust against depression ( Figure 5B ) and pruning ( Figure 3E ).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism linking LTP to synaptic stabilization, and LTD to destabilization, is likely to involve several processes. Synaptic tenacity is known to be affected by trans-synaptic proteins such as Neuroligin-1 and SynCAM-1 ( Zeidan and Ziv, 2012 ; Körber and Stein, 2016 ), PSD-95 ( De Roo et al, 2008 ; Cane et al, 2014 ), ubiquitin protein ligase E3A ( Kim et al, 2016 ), ensheathment of the synapse by astrocyte processes ( Bernardinelli et al, 2014 ) and many other local factors. It may be a combination of local physical changes and distributed network effects, such as the recurrent reactivation of a specific circuit ( Wei and Koulakov, 2014 ; Novitskaya et al, 2016 ), which makes once potentiated synapses robust against depression ( Figure 5B ) and pruning ( Figure 3E ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to their role in other tissues, SynCAMs are known synaptic cell adhesion molecules: through homophilic and heterophilic interactions between their extracellular domains, these molecules form trans-synaptic complexes 30 31 , and it has been demonstrated that these complexes are involved in synaptogenesis (for review see ref. 32 ) and also in synapse stabilisation 33 34 .…”
Section: Discussionmentioning
confidence: 99%
“…In terms of physiological maturation, neurexins are critical synaptic organizers as first shown in vivo by the result that α-neurexin loss impairs evoked neurotransmission (Missler et al, 2003). Additional evidence for instructive roles of trans-synaptic organizers in synapse development comes from studies of another class of postsynaptic neurexin ligands called LRRTM proteins (de Wit and Ghosh, 2016), LAR phosphotyrosine phosphatases that signal on the presynaptic side (Takahashi and Craig, 2013), and SynCAM 1, which is preferentially postsynaptic and required and sufficient to control the number of excitatory synapses in vivo (Park et al, 2016; Korber and Stein, 2016; Robbins et al, 2010). The subsynaptic functions of these and other adhesion molecules could include localization or retention of pre- and post-synaptic nanodomains at developing and mature synapses, altering the geometry of the cleft and hence the diffusion of neurotransmitters, or modulating presynaptic Ca channel function (Freche et al, 2011; Glebov et al, 2016; Tong et al, 2017; Wahl et al, 1996).…”
Section: Relevant Structures and Their Patterning In The Three Synaptmentioning
confidence: 99%